Four critiques of the redistribution hypothesis: An assessment - Branko Milanovic (Luxembourg Income Study (LIS), 2010)
The reformulation of the median voter hypothesis and its testing proposed in Milanovic (2000) has been criticized from four different perspectives. The critiques are discussed and assessed.
Keywords: D31; E62; 330; Median voter; Income distribution; Redistribution; Medianwähler-Modell; Einkommensverteilung; Einkommensumverteilung